Emission permits and the dynamics of clean and dirty firms in an evolutionary competition model. (1st April 2019) - Antoci, Angelo; Borghesi, Simone; Iannucci, Gianluca; Russu, Paolo
Abstract: Emission Trading Systems (ETSs) are today regarded as the pillar of market‐based environmental policies in many countries. This paper studies the impact of an ETS on the dynamics of the market made up of two types of firms: clean and dirty. Using an evolutionary context, we study how the share of clean firms evolves at different parameter values, such as increasing values of the permits' price floor, and show that an ETS can have positive effects on the diffusion of the clean technology. However, numerical simulations show that under specific parameter values the opposite result may emerge with clean firms leaving the market.